2009
DOI: 10.2135/cropsci2008.06.0361
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit Effect on the Relationship between Temperature during the Seed Fill Period and Soybean Seed Oil and Protein Concentrations

Abstract: Since most soybean [Glycine max (L.) Merr.] seed is processed into meal and oil, there is a growing concern about environmental effects on soybean seed composition. The aim of this work was to investigate how water deficit affects the well‐known relationship of soybean seed oil and protein concentrations with temperature and, alternatively, with solar radiation during seed fill. We analyzed oil and protein data from multienvironment trials in Argentina (latitude 29° to 38° S). Multiple linear regressions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 26 publications
(80 reference statements)
7
69
2
Order By: Relevance
“…From the daily climatic data, the following variables were generated for each environment: average daily mean air temperature during seed filling (Tm R5R7 ); cumulative solar radiation during seed filling (Sr R5R7 ), calculated as the sum of daily solar radiation in that period; and precipitation minus potential evapotranspiration during the whole reproductive period (pp-PET R1R7 ). The variable pp-PET R1R7 was used as a simple indicator of water availability in the evaluated period, since water balance from the whole reproductive period considers water storage in the soil profile, which could influence water availability during grain filling (Carrera et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the daily climatic data, the following variables were generated for each environment: average daily mean air temperature during seed filling (Tm R5R7 ); cumulative solar radiation during seed filling (Sr R5R7 ), calculated as the sum of daily solar radiation in that period; and precipitation minus potential evapotranspiration during the whole reproductive period (pp-PET R1R7 ). The variable pp-PET R1R7 was used as a simple indicator of water availability in the evaluated period, since water balance from the whole reproductive period considers water storage in the soil profile, which could influence water availability during grain filling (Carrera et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely documented that soybean seed composition varies with environmental factors, especially during the seed filling period when accumulation of the seed chemical components occurs (Wolf et al, 1982;Wilson, 2004;Carrera et al, 2009Carrera et al, , 2011. The relationship of protein contents (the sum of all amino acids) with temperature (Piper & Boote, 1999;Wilson, 2004) and water availability (Rose, 1988;Boydak et al, 2002;Kumar et al, 2006;Carrera et al, 2009) has also been studied, but results have shown dissimilar patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Argentina the grain quality is of great interest since 73% of the soybean production is exported as processed soybean meal and oil, making Argentina the world's leading exporter of these specialties (Carrera et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers determined that the amount of protein decreases with soil water deficit (Specht et al 2001, Boydak et al 2002, Carrera et al 2009). Contrarily, Kumar et al (2006) and Rotundo and Westgate (2010) found that the protein content increases with increasing water deficit.…”
mentioning
confidence: 99%